The Multi Business Model Innovation Approach Part 1 - Lindgren, Peter (Taylor & Francis, 2018)
It is argued in most academic literature that Business Model (BM) is a general model for how any business runs or should be run, it is the "blueprint of the business". Conversely we argue that no business has just one BM, one model on which it runs all its business or intends to run its business. In other words the BM can be used for "as-is" and the "to-be" businesses. However our research, in contrast to the other BM frameworks, indicates that businesses have more BMs - both "as-is" and "to-be" BMs - the multi business model approach. This was already theoretically indicated by Markides and Charitou in 2004, and again in the Casadesus-Masanell and Ricart model of 2010, but sadly no one in the BM community has followed up on this since then. It could have made a breakthrough in our understanding of BMs, Business Model Innovation (BMI) and Strategic BMI. The Multi Business Model Innovation Approach addresses the concerns in the BM community and in BMI practice to just focus on the ideation and conceptualization of BMs. "BM canvassing", innovating BM building blocks or BM dimensions when carrying out BMI, so-called "blind business model innovation", is not sufficient to run and understand a business today. BMs and BMI must address all the different levels in a business. All BMs are objects to BMI and should be used to maximize the performance and sustainability of the business. The core business and all levels BMs, such as BM dimension components, BM dimensions, BM portfolio, and Business Model Ecosystem (BMES), should all be considered for BMI. The book addresses and documents a gap in BM research and the BM community - but also proposes a generic definition and language of a BM and BMI layers. The significance and importance of this work is related to significant and unexplored possibilities that BMI offers today, and can offer tomorrow. When we thoroughly understand all levels, dimensions and components of the business and its business models, and we are able to communicate, work and innovate with business models at all levels together, then a next step in BM and BMI research and practice can be taken. It is proposed that any BMs are related to seven dimensions- value proposition, user and/or customer, value chain functions (internal), competence, network, relations and value formulae. It is further proposed that seven different levels of a BMI from the most detailed level - the BM dimension component - to the BM dimension, BM, BM portfolio, business, and the vertical and horizontal business model ecosystem layer - and these can be objects to BMI. Conceptually, the Business Model Cube was formed using the seven dimensions which could be used both in a 2D and a 3D version.